2017
DOI: 10.1037/hea0000456
|View full text |Cite
|
Sign up to set email alerts
|

Expectations for antibiotics increase their prescribing: Causal evidence about localized impact.

Abstract: Objective: Clinically irrelevant but psychologically important factors such as patients' expectations for antibiotics encourage overprescribing. We aimed to (a) provide missing causal evidence of this effect, (b) identify whether the expectations distort the perceived probability of a bacterial infection either in a preor postdecisional distortions pathway, and (c) detect possible moderators of this effect. Method: Family physicians expressed their willingness to prescribe antibiotics (Experiment 1, n 1 ϭ 305)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 34 publications
(41 reference statements)
1
71
0
Order By: Relevance
“…During a primary care consultation, the patient’s behaviour exerts a powerful influence on whether a physician will withhold or prescribe antibiotics (Macfarlane, Holmes, Macfarlane, & Britten, 1997). Patient expectations for antibiotics have been identified as a particularly important factor in the overprescribing of antibiotics in primary care (McNulty, Nichols, French, Joshi, & Butler, 2013; Pan et al , 2016; Sirota, Round, Samaranayaka, & Kostopoulou, 2017). Patients who expect antibiotics from a physician almost always receive them (McNulty et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During a primary care consultation, the patient’s behaviour exerts a powerful influence on whether a physician will withhold or prescribe antibiotics (Macfarlane, Holmes, Macfarlane, & Britten, 1997). Patient expectations for antibiotics have been identified as a particularly important factor in the overprescribing of antibiotics in primary care (McNulty, Nichols, French, Joshi, & Butler, 2013; Pan et al , 2016; Sirota, Round, Samaranayaka, & Kostopoulou, 2017). Patients who expect antibiotics from a physician almost always receive them (McNulty et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Patients who expect antibiotics from a physician almost always receive them (McNulty et al , 2013). Building on these findings, Sirota et al (2017) provided causal evidence that patients’ expectations to receive antibiotics are sufficient to actuate physicians to prescribe them – even when they are not clinically justified (i.e., inappropriate).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that those who incorrectly believed that antibiotics will work for viral infections were more likely to expect antibiotics from prescribers [30,31]. Patients' expectations of antibiotics are found to be an important predictor of antibiotic prescribing [32,33]. Expectations for antibiotics for common cold were found among older adults when they felt sick enough to visit a physician, although most of them disagreed that antibiotics could speed the recovery [24].…”
Section: Introductionmentioning
confidence: 99%
“…These interventions have the potential to support the government's ambition to reduce inappropriate antibiotic consumption [1], particularly since interventions that help to both reduce referrals to GPs and inform patients on the appropriate use of antibiotics (including when they are necessary or unnecessary) may reduce patient expectation to receive antibiotics for self-limiting infections, and in turn reduce pressure on GPs to prescribe antibiotics when they are not needed [14]. The leaflet, which is available at no cost from the TARGET website (www.rcgp.org.uk/targetantibiotics), can support efforts to raise awareness on the appropriate use of antibiotics, use of available resources, and signpost to sources of advice and information (for instance, directing patients and customers to the Antibiotic Guardian website, a pledge-based campaign website) (www.antibioticguardian.com).…”
Section: Discussionmentioning
confidence: 99%